2020
DOI: 10.3390/math8071131
|View full text |Cite
|
Sign up to set email alerts
|

On the Dual and Inverse Problems of Scheduling Jobs to Minimize the Maximum Penalty

Abstract: In this paper, we consider the single-machine scheduling problem with given release dates and the objective to minimize the maximum penalty which is NP-hard in the strong sense. For this problem, we introduce a dual and an inverse problem and show that both these problems can be solved in polynomial time. Since the dual problem gives a lower bound on the optimal objective function value of the original problem, we use the optimal function value of a sub-problem of the dual problem in a branch and bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In particular, for w 1 = 1 there exists a solution such that w j = X(1, j) and such that w j = Ỹ(1, j). In other words, the section of the set of solutions by the plane w 1 = 1 lies inside the parallelepiped described by the inequalities (13) and has at least one common point with each of its faces. Therefore, by Lemma 3 the center of this parallelepiped is an interior point of the set of solutions to the initial system of inequalities and is a solution to the initial system.…”
Section: Methods For Solving the Efficient System Of Inequalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for w 1 = 1 there exists a solution such that w j = X(1, j) and such that w j = Ỹ(1, j). In other words, the section of the set of solutions by the plane w 1 = 1 lies inside the parallelepiped described by the inequalities (13) and has at least one common point with each of its faces. Therefore, by Lemma 3 the center of this parallelepiped is an interior point of the set of solutions to the initial system of inequalities and is a solution to the initial system.…”
Section: Methods For Solving the Efficient System Of Inequalitiesmentioning
confidence: 99%
“…The goal is to schedule the jobs to proceed on the machine, minimizing some objective functions. A wide variety of studies of this problem can be found for such objective functions as the total or maximum lateness [8,9], the weighted number of tardy jobs [10], the total (weighted) completion time [11,12] or any arbitrary non-decreasing function of the completion time [13]. The idea is that the objective function is known and should be maximized or minimized.…”
Section: Introductionmentioning
confidence: 99%
“…Lazarev et al [15] consider the single-machine problem with given release dates and the objective to minimize the maximum job penalty. While this problem is NP-hard in the strong sense, they introduce a dual and an inverse problem, which can be both polynomially solved.…”
mentioning
confidence: 99%